Determinasi Minat Belajar: Analisis Praktik Kerja Industri dan Prestasi Belajar - Saputra, Raihan (Siber Nusantara Publisher, 2023)
Abstract: Determination of Interest in Learning Analysis of Industrial Work Practices and Learning Achievement is a scientific article in the literature study within the scope of Education. This article aims to build a hypothesis of the influence between variables that it will use in further research. In addition to seeing the effect of industrial work practices and learning achievement on learning interest. Research objects in online libraries, Google Scholar, Mendeley, and other academic online media. Sourced from previous research that is relevant to this research. A descriptive qualitative method, library research, from e-books and open access e-journals. The results of this article are: 1) Industrial Work Practices are related to Interest in Learning; 2) Learning Achievement is related to Learning Interest; and 3) Industrial Work Practices related to Learning Achievement. Abstrak: Determinasi Minat Belajar: Analisis Praktik Kerja Industri dan Prestasi Belajar adalah artikel ilmiah studi pustaka dalam ruang lingkup ilmu Pendidikan. Tujuan artikel ini membangun hipotesis pengaruh antar variabel yang akan digunakan pada riset selanjutnya. Selain itu untuk melihat pengaruh praktik kerja industri dan prestasi belajar terhadap minat belajar. Objek riset pada pustaka online, Google Scholar, Mendeley dan media online akademik lainnya. Bersumber dari penelitian terdahulu yang relevan dengan penelitian ini. Metode kualitatif deskriptif, library research, dari e-book dan open access e-journal. Hasil artikel ini yaitu: 1) Praktik Kerja Industri berhubungan terhadap Minat Belajar; 2) Prestasi Belajar berhubungan terhadaap Minat Belajar; dan 3) Praktik Kerja Industri berhubungan terhadap Prestasi Belajar.